PERANCANGAN SISTEM INFORMASI DALAM PELAYANAN PUBLIK KANTOR LURAH BABUSSALAM - CANDRA, DORI (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2024)
This research highlights the importance of quality public services in government administration, with a focus on the Babussalam Village Head Office. Currently, the Babussalam Lurah Office is facing challenges in its information system, which impacts on the efficiency and effectiveness of public services. The objective of this data collection is to analyze the information system and create a new information system that is more efficient. It is hoped that with the implementation of the Information Service System (APSI), the quality of public services at the Babussalam Lurah Office can be improved.